An Analysis of English Students' Learning Motivation Factors in E-Learning Class during Covid-19 Pandemic - Muhamad Kadapi; Dila Charisma; Hanif Nurcholish Adiantika (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Muhammadiyah Cirebon, 2021)
This research aimed to investigate English students’ learning motivation in participating online learning through e-learning class at one senior high school in Cirebon and to know the affecting factor of students’ motivation. Qualitative research was used in this research which descriptive qualitative as research design. The source of data was the main data which in the collecting of data was obtained through observation, interview and documentation process. To analysis the data was done through there steps namely data reduction, data display and verification, then the data triangulation and source were used as a means to checking the validity of the data. The results of the research described that the students have a decrease in their motivation for learning because during Covid-19 Pandemic students are more comfortable and enthusiastic in learning by face to face learning rather than online learning through e-learning class, the students have difficulty in understanding the material, learning become less interactive, the delivery of material become less varied and the lack of the teacher in response the students was considered the dominant factors affects English students’ motivation during Covid-19 pandemic.